2005
DOI: 10.1021/ja055635i
|View full text |Cite
|
Sign up to set email alerts
|

Critical Influence of Adsorption Geometry in the Heterogeneous Epoxidation of “Allylic” Alkenes:  Structure and Reactivity of Three Phenylpropene Isomers on Cu(111)

Abstract: It has long been conjectured that the difficulty of heterogeneously epoxidizing higher alkenes such as propene is due to the presence in the molecule of "allylic" H atoms that are readily stripped off by the oxygenated surface of the metal catalyst resulting in combustion. Here, taking advantage of the intrinsically higher epoxidation selectivity of Cu over Ag under vacuum conditions, we have used three phenylpropene structural isomers to examine the correlation between adsorption geometry and oxidation chemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 24 publications
3
34
0
Order By: Relevance
“…So, as a model surface in this study, a RuO 2 (110) surface coverage of 0.5 (single O ot oxygen species over surface in this model) has been studied to simulate the effect of oxygen presence for propylene epoxidation reaction. Thus, the required space for propylene adsorption is generated for the formation of surface intermediate which is crucial for epoxidation of alkenes as stated in the literature [19,[24][25][26][27].…”
Section: Ruo 2 (110) and Ruo 2 -O Ot (110) Surface Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…So, as a model surface in this study, a RuO 2 (110) surface coverage of 0.5 (single O ot oxygen species over surface in this model) has been studied to simulate the effect of oxygen presence for propylene epoxidation reaction. Thus, the required space for propylene adsorption is generated for the formation of surface intermediate which is crucial for epoxidation of alkenes as stated in the literature [19,[24][25][26][27].…”
Section: Ruo 2 (110) and Ruo 2 -O Ot (110) Surface Modelsmentioning
confidence: 99%
“…Comparative theoretical studies on propylene epoxidation over Ag(111) and Cu(111) surfaces also revealed the importance of the surface intermediates and the effectiveness of the Cu(111) surface in propylene epoxidation [19,[25][26][27]. Besides the formation of the surface intermediates, the basic character of the adsorbed oxygen over the metal surface directs the reaction route to either oxametallacycle intermediates or ally radical leading to the complete combustion reaction [8,25].…”
Section: Introductionmentioning
confidence: 99%
“…[22,27,33] Activation of the allylic proton (step A) leads to formation of a radical intermediate that subsequently would generate acrolein and/or CO 2 , depending on the operating reaction conditions. [7,[33][34][35][36][37] Activation of the primary (step C) or secondary (step B) vinylic carbon atoms ends up with formation of a cyclic structure commonly referred as oxametallacycle or OMMP, where M stands for the metal atom inserted and the last letter is the initial letter for the olefin precursor, propylene (P) in this case. From the OMMP complexes, carbonyl species are formed by transferring a vinylic hydrogen (steps D and F); whereas by epoxidation (step E)…”
Section: Introductionmentioning
confidence: 99%
“…The low selectivity of silver-based catalysts towards propylene epoxide has been related to the limited formation of the OMMP precursors (steps B and C), while the competitive allylic hydrogen abstraction (step A) is usually kinetically and thermodynamically more favorable. [33][34][36][37] In the case of ethylene, (R = H), the absence of allylic hydrogen atoms drastically decreases the formation of the radical intermediate that would arise from vynilic hydrogen abstraction.…”
Section: Introductionmentioning
confidence: 99%
“…However, core excitation spectroscopy combining core information with that of local binding near the excitation atom can provide a rather reliable basis to discriminate between atoms in different coordination environments and analyze their binding properties. This has been shown successfully for free and adsorbed molecules [8][9][10], for surfaces [11,12], and for bulk and interfacial systems [13][14][15][16][17] where theoretical Density-Functional Theory (DFT) studies of corresponding excitation spectra in comparison with (angle-resolved) Near-Edge X-ray Absorption Fine Structure (NEXAFS) measurements can yield very detailed information on a local atomic level.…”
Section: Introductionmentioning
confidence: 99%